(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
HCV infection is a major health problem in Egypt. Studies using safe natural products BlueÂ greenÂ® tablet showed its antiviral effect. Polymorphisms in the interleukin-28B (IL28B) geneÂ are associated with outcomes from infection with HCV. The rationale of the present study is toÂ evaluate the potential role of interleukin 28B gene polymorphism (IL28B) and natural immune enhancer treatment response in chronic HCV patients. This study included 100 chronic HCVÂ patients. Patients were classified into two groups: Group I, fifty patients with cirrhosis andÂ advanced liver disease. Patients were unfit INF/ Ribavirin: Group II, fifty patients who refusedÂ INF/Ribavirin. Patients were treated with combination of natural products of Blue greenÂ® tabletÂ (4 tablets daily which equivalent to 100 mg AFA/30 kg BW), vitamin D, tea spoon field paste ofÂ black seeds, olive oil and honey. Alanine Aminotransferase (AST), Aspartate AminotransferaseÂ (ALT), complete blood count (CBC) were measured in the two groups. Detection of HCV-RNAÂ level by quantitative PCR was done before & after 3, 6, 12 and 18 months of treatment. GenomicÂ DNA extracted from all the 100 patientâ€™s blood samples was analyzed for the rs12979860 SNP of IL28B using a real-time polymerase chain technique incorporating SYBR Green. The resultsÂ showed that, the activities of hepatic marker enzymes (AST and ALT), complete blood picturesÂ (Hb, WBCs and Platelets), HCV RNA PCR, IL 28-B gene polymorphism were non-significantlyÂ (p>0.05) differences when compared untreated patients (Group I) and treated patients (Group ) were CC genotype before treatment was 8 (34%) & was 13 (26%) after treatment, CT genotypeÂ before treatment was 26 (52%) & was 28 (56%) after treatment, TT genotype before treatmentÂ was 7 (14%) & was 9 (18%) after treatment. Also, there were non-significant (p>0.05)Â differences between responder & non-responder in treated patients. In conclusion, the treatment with natural immune enhancer in chronic HCV patients showed no significance correlation withÂ IL 28 gene polymorphism